(untitled) (Comprehensive Journal of Science, 2026)
Diabetes mellitus can be considered as a chronic metabolic disorder categorized by the level of blood glucose which resulting from the defects of insulin secretion, insulin action, or both. Therefore, it is a known as a primary cause of morbidity and mortality in the worldwide, because its prevalence continues to rise, mainly in developing countries. Understanding the changes of biochemical associated with diabetes is crucial for disease management and the prevention of complications. This research aims to examine the relationship between, the serum of diabetes mellitus and calcium level. The research has conducted on 100 diabetic patients at the Endocrinology and Diabetes center in Emsallata, and ran on 48 males and 52 females. The research showed no statistically significant relationship between the levels of calcium, and the presence of diabetes mellitus.